Filantropi Islam di Komunitas Muslim Tionghoa Surabaya: Ikhtiar Manajemen Zakat untuk Kesejahteraan dan Harmoni Sosial - Choirul Mahfud (State Institute of Islamic Studies (IAIN) Salatiga, 2018)
The Chinese Muslim community in Surabaya takes a role in various social activities, through Islamic philanthropy programs in the zakat aspect. This study using qualitative data from several observation, interviews, reference books, news, journals and opinions in mass media as well as other relevant sources. This study focuses on the following questions: First, how is the effort to optimize Islamic philanthropy in the zakat program for community welfare in the Chinese Muslim community in Surabaya? Secondly, how is the management of professional zakat efforts to realize the community in the Chinese Muslim community? Third, how to build zakat movement in Indonesia? The results showed; first, the optimization of Islamic philanthropy in the Chinese Muslim community in Surabaya through the zakat program has been done, but still needs to be improved. Second, professional management of zakat is needed to realize society. How to involve a lot of professionals by using good management technology and systemic. Third, building the zakat movement in Indonesia among Chinese Muslim and non-Chinese Muslim and government partners to achieve optimal results.